Illustrated atlas of the Himalaya - Zurick, David (UPCC book collections on Project MUSE., 2006)
The Himalaya inspire the notion of Shangri-la and are world renowned for their exquisite mountain scenery and the ancient cultures that tenaciously inhabit this harsh and sublime landscape. Home to all fourteen of the world's highest peaks, including Mount Everest, and some of its deepest gorges, the region is a trove of biological and cultural diversity. A sweeping overview of the geography, economics, politics, and culture of this spectacular region, the Illustrated Atlas of the Himalaya is the first full-color, comprehensive atlas of contemporary land and life in the Earth's highest mounta.